Metal Injection Moulding Process Simulation for Orthodontic Bracket Application - Shinta Virdhian; Sina Jamilah; Sugeng Supriadi; Bambang Suharno (Balai Besar Bahan dan Barang Teknik, 2017)
Metal Injection Moulding (MIM) process is one of effective process to produce complex shape product in the mass production scale. MIM process had been applied in many applications such as consumer product, automotive, biomedical etc. In this work, an orthodontic bracket is manufactured using MIM process. Before manufacturing process, simulation using commercial software Sigmasoft is done to evaluate the design and optimize the process parameters. Some parameters are inserted to run simulations in order to get optimum process condition for MIM process. Parameters to be optimized include the mold and feedstock temperature, cycle time and pressure during the injection process. In this simulation, the melt temperature is 190 °C and mold temperature is varied from 90-150 °C based on the reference from Catamold. The optimum mold temperature is 90 °C and filling simulation shows that the melt can still fill the cavity in that temperature with optimum filling time 2.5 s. From the simulation, the existing design can be improved by reducing the size of the runner and removing the sharp corner.Proses Metal Injection Moulding (MIM) merupakan salah satu proses yang efektif untuk pembuatan produk logam yang memiliki bentuk yang rumit dan skala produksi massal. Proses MIM telah digunakan pada banyak aplikasi seperti produk rumah tangga, otomotif, biomedikal dan lain-lain. Dalam penelitian ini, braket ortodontik dibuat melalui proses MIM. Sebelum proses manufaktur, simulasi injeksi dilakukan dengan menggunakan software komersial Sigmasoft untuk mengevaluasi desain dan optimasi parameter proses. Beberapa parameter proses dimasukkan ke dalam simulasi untuk mendapatkan kondisi proses yang optimum, antara lain temperatur injeksi,temperatur mold, waktu proses, dan tekanan selama proses injeksi. Dalam simulasi ini, temperatur injeksi 190 °C dan temperatur mold divariasikan 90-150 °C dan waktu pengisian dari 0,5-3 detik. Hasil simulasi menunjukkan temperatur mold optimum pada 90 °C dan feedstock masih bisa mengisi rongga dengan waktu pengisian 2,5 detik. Dari hasil simulasi aliran menunjukkan desain yang ada dapat dioptimalkan dengan mengurangi ukuran runner dan bentuk yang tajam.